ANALISIS FENOMENA SOSIAL BATU AKIK (STUDI PADA MASYARAKAT (PENJUAL-PEMBELI) DI PUSAT PENJUALAN BATU AKIK PALEMBANG) - Boty, Middya (JIA (Jurnal Ilmu Agama), 2015)
This research aims to analyse the meaning of gemstones and their impact to the society. Thiis research uses qualitative approaceh with Miles and Huberman (1992) point of view on the meaning of symbols. The research finding shows that there are several meanings on the gemstone booming in the center of gemstone market in Palembang, among others are:; gemstones are the symbol of salvation, fortune, affection, security, social statuses, and charisma. Meanwhile the gemstone booming has an impact on social and environtment.